GENDER DECONSTRUCTION IN AL KHALLAT+ - Muhammad Irfan Maulana; Falih Hilmi Adi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Alkhallat+ is one of the films from Saudi Arabia published on Netflix featuring four themes about deceit. The interesting part of this film is the existence of misogynistic values by the author that can bring out the opposite meaning of favoring women. This research will analyze the gender issue in the film using Jacques Derrida's Deconstruction theory, which brings the concept of binary opposition to gender. This theory is used to explore the idea of deconstruction reflecting misogynistic values in the movie. The result reveals that